Penerapan Hadis Larangan Dua Akad Dalam Satu Transaksi Di UMKM Batik Tulis Sumber Ayu Probolinggo - Salsabilah, Firyal; Ghozali, Lathoif (Jurnal Ilmiah Ekonomi Islam, 2024)
Contracts have a very significant position in activities in the fields of economics, business and finance. And the influence on goods is very large, so that muamalah transactions are said to be valid if the contract carried out meets the requirements and is harmonious. Sharia economic literature does not allow two contracts in one transaction (two in one). Many hadiths explain that the Prophet prohibited two contracts in one transaction which could cause the price set to be unclear. This research is qualitative research with the type of research using field studies. A contract is an activity carried out by two parties who mutually agree to be bound and obliged to carry out their obligations agreed upon at the beginning of the transaction in accordance with sharia. The verses that explain the contract are Q.S Al-Maidah verse 1, Q.S Ali Imran verse 76, and Q.S An-Nisa verse 29. Not only verses from the Qur'an, there are also hadiths that explain the contract, namely the Sahih Bukhari hadith 1967, Sahih Bukhari 7903, and Musnad Ahmad 7903. In connection with the Prophet's prohibition on carrying out two contracts in one transaction, the sale and purchase contracts established at the Sumber Ayu Batik Tulis UMKM do not recommend that consumers carry out two contracts in one transaction. Because it can cause gharar in the products being sold